Caracterización tecnológica de veinte Especies maderables de la Selva Lacandona - Bárcenas Pazos, Guadalupe M. (Instituto de Ecología, A.C., 1995)
The technological characterization of twenty wood species from the Lacandona rain-forest was carried out to generate the necessary technical information on lesser-known tropical wood species from Mexico. Those species were selected based on their trunk shape, distribution and abundance. Tests on physical and mechanical properties, sawing, durability, and natural resistance against biodegradation were performed. Results are presented in both tables per each type of test and technological data sheets per individual species. A methodology to study tropical species properties was developed based on specifications for temperate-regions woods.